Orthophosphate Interactions with Destabilized PbO(2) Scales - DeSantis, Michael K. (Environ Sci Technol, 2020)
This research presents two case studies in which a change in the disinfectant from free chlorine to chloramine caused an increase in lead corrosion. In both systems, the predominantly tetravalent lead (PbO(2)) scales destabilized as a result of disinfectant change. Orthophosphate corrosion control was used in both systems, and the effect of this treatment chemical on the destabilized PbO(2) scales was examined. The absence of chemical reactivity between PbO(2) and phosphorus is well known, and this research confirms that phosphorus does not interact with the legacy PbO(2) scales. Instead, phosphorus and calcium were found to permeate through the destabilized PbO(2) material and react with divalent lead [Pb(II)] at the surface of a basal litharge (PbO) layer. This reaction precipitated a crystalline lead phosphate in both systems, which could not be specifically identified by any known powder diffraction files. Further analysis suggested that the compound formed was not the typically modeled hydroxypyromorphite but rather a calcium-substituted hydroxypyromorphite. During scale formation, calcium is frequently bound to the Pb(II) phosphate crystal lattice structure, causing measurable crystal lattice distortion in powder X-ray diffraction patterns. The results of this study illustrate the longevity of legacy scales and how disequilibrium compounds persist long after treatment changes have been made.